PERSEPSI MAHASISWA ILMU KOMUNIKASI UNAND MENONTON FILM DIRTY VOTE TERHADAP KEPUTUSAN MEMILIH PASCA PEMILU 2024 - Laysani, Hafsyah Bemeiza (Universitas Teuku Umar, 2025)
Film is a mass communication medium that is used to convey messages to audiences by telling stories, presenting events, music, drama and other technical presentations. Dirty Vote describes a number of dishonest activities that occur throughout the election process, such as intimidation of voters, vote fraud, and manipulation of results. The choice of broadcast time for this film, which was close to the day when the election was held, made this film excitedly discussed by the public. The election competition which was getting hotter before the election was made even hotter with the release of this film. Research conducted qualitatively. Data was collected through in-depth interviews and focus group discussions. There were four informants interviewed and all of them had watched it the film “Dirty Vote”. Reading positions are differentiated into dominant- hegemonic, negotiation, and opposition. Most reading positions is negotiation. Interviews with four informants watching the movie Dirty Vote found that Differences in reception results are caused by environmental, family and experience factors of each informant